COLOUR IDIOMS IN ENGLISH, SPANISH AND UZBEK LANGUAGES (International Engineering Journal For Research & Development, 2020)
This article is about similarities and differences of using color idioms in three languages. A comparartiveanalyse allows us to conclude that there are many idioms and phraseological units with the use of color, but not all colors are the same in Spanish, English and Uzbek languages.